An Analysis of Reading Difficulties in English Texts among Tenth-Grade Students at SMA Negeri 1 Praya Barat - Riska Putri, Riska; Hendriani, Ria (Tirai Edukasi : Jurnal Pendidikan, 2024)
This study investigates the difficulties experienced by tenth-grade students in comprehending English texts at SMA Negeri 1 Praya Barat. Employing a descriptive qualitative design, the research collected data through classroom observation, structured interviews, and an assessment rubric administered to 37 students. The findings reveal that students encountered major challenges in vocabulary recognition, understanding text content, identifying main ideas, making inferences, and reading fluency. These difficulties stemmed from both internal factors—such as limited vocabulary, low motivation, anxiety, and slow information processing—and external factors, including lack of reading practice, insufficient support from teachers or family, negative prior experiences, and cultural differences within texts. The results suggest that reading comprehension issues are multidimensional, encompassing linguistic, cognitive, affective, and socio-cultural aspects. The study highlights the importance of tailored pedagogical approaches that integrate vocabulary enrichment, motivational strategies, and culturally relevant materials to foster improved reading outcomes..